2007
DOI: 10.1158/0008-5472.can-07-1022
|View full text |Cite
|
Sign up to set email alerts
|

γ-Secretase Inhibitor Prevents Notch3 Activation and Reduces Proliferation in Human Lung Cancers

Abstract: Notch receptors are key regulators of development by controlling cell-fate determination in many multicellular organisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
201
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(217 citation statements)
references
References 30 publications
15
201
1
Order By: Relevance
“…Previous studies also documented that Notch1 was frequently expressed in lung cancer and correlated with the malignancy of NSCLC (Collins et al, 2004). In contrast, recent studies have demonstrated reduced or even undetectable Notch1 expression in NSCLC, implying its tumor-suppressive role in NSCLC Konishi et al, 2007). To explore the precise mechanism involved in the interaction between endothelial Dll4 and Notch receptors of NSCLC, we examined the mRNA levels of Notch in A549 cells cocultured with ECs.…”
Section: Resultsmentioning
confidence: 95%
“…Previous studies also documented that Notch1 was frequently expressed in lung cancer and correlated with the malignancy of NSCLC (Collins et al, 2004). In contrast, recent studies have demonstrated reduced or even undetectable Notch1 expression in NSCLC, implying its tumor-suppressive role in NSCLC Konishi et al, 2007). To explore the precise mechanism involved in the interaction between endothelial Dll4 and Notch receptors of NSCLC, we examined the mRNA levels of Notch in A549 cells cocultured with ECs.…”
Section: Resultsmentioning
confidence: 95%
“…DAPT reduces ductal carcinoma in situ mammosphere formation (Farnie et al, 2007) and pancreatic cancer cell growth (Kimura et al, 2007). Another g-secretase inhibitor, MRK-003, reduces tumour cell proliferation, inhibits serum independence, and induces apoptosis of lung cancer cell lines in vitro and in vivo using mouse xenograft models (Konishi et al, 2007). Thus, the g-secretase complex is now becoming an accepted target in cancer therapy, in particular, with regard to Notch signalling (Shih and Wang, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that γ-secretase inhibitors would have caused GBM TIC cell death was mainly based on recently published literature, which reported that γ-secretase inhibitors kill Kaposi's tumor cell lines (38), enhance chemotherapy-induced apoptosis in colon cancer cells (39) and in myeloma cells (40), and reduce the proliferation of lung cancer cells (41).…”
Section: Discussionmentioning
confidence: 99%